(untitled) (Journal SCIENCEVOLUTION, 2025)
The literature on urban and riparian edges addresses the physical, social, historical, political, and technological components that shape these spaces in a fragmented manner, which has hindered an integrated understanding of their dynamics and tensions. Therefore, this systematic review aimed to identify the analytical dimensions employed in scientific research, recognize the cross-cutting tensions that structure these territories, and propose integrative theoretical constructs to guide future studies. The PRISMA 2020 methodology was applied, and a meta-synthesis was conducted. The search in SCOPUS, Web of Science, and SciELO retrieved 92 studies published between 2015 and 2025; after the screening and evaluation process using MMAT, 10 medium- and high-quality articles were selected. The results showed a predominance of socio-cultural and historical-temporal analyses, while the technological and economic-political dimensions appeared less frequently. Three central tensions were identified: conservation-development, inclusion-exclusion, and access-restriction, which transversally affected all dimensions. The meta-synthesis allowed for the synthesis of the evidence into five theoretical constructs (biophysical substrate, socio-symbolic fabric, temporal stratification, arena of governance and interest, and technical mediation system) that, when articulated, formed a multidimensional systemic model of riparian edges. In conclusion, the review revealed the absence of integrative frameworks and the need for transdisciplinary approaches that overcome partial analyses. The study recommended strengthening comparative research, incorporating monitoring technologies, and deepening studies on governance and spatial justice to guide more inclusive and sustainable public policies and urban projects.